2011
DOI: 10.1161/circheartfailure.110.958520
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Trial of Single-Drug Versus Dual-Drug Immunosuppression in Heart Transplantation

Abstract: Addition of mycophenolate to single-agent immunosuppression did not provide an advantage over single-agent immunosuppression in terms of rejection, allograft vasculopathy, or 3-year survival. Corticosteroids, which have traditionally been a mainstay of therapy, were successfully discontinued in all patients. These conclusions are tempered by the limited statistical power associated with a sample size of only 150 patients. Clinical Trial Registration- URL: http://www.clinicaltrials.gov. Unique identifier: NCT00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…Importantly, modification of immunosuppressive therapy in Group I was not associated with increased incidence of rejections (P = 0.0534). These findings are consistent with the results of the TICTAC trial 24 which showed that addition of MMF to single-agent immunosuppression does not provide any advantage over single-agent immunosuppression in terms of rejections. Similar results were also found by Teuteberg 25 who reported a regimen consisting of a dose reduced MMF in patient after HTx.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, modification of immunosuppressive therapy in Group I was not associated with increased incidence of rejections (P = 0.0534). These findings are consistent with the results of the TICTAC trial 24 which showed that addition of MMF to single-agent immunosuppression does not provide any advantage over single-agent immunosuppression in terms of rejections. Similar results were also found by Teuteberg 25 who reported a regimen consisting of a dose reduced MMF in patient after HTx.…”
Section: Discussionsupporting
confidence: 90%
“…2,3 The well-known adverse effects of tacrolimus include nephrotoxicity, 4 hypertension, 5 neurotoxicity, [6][7][8][9][10] and glucose intolerance. 11,12 Posterior reversible encephalopathy syndrome was f irst reported in 1996 by Hinchey and colleagues, 13 who described a reversible syndrome associated with headache, altered mental function, seizures, and visual disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions are tempered by the limited statistical power associated with a sample size of only 150 patients. 4 Chronic Kidney Disease and the Risk of Heart Failure in Men Summary: Individuals with chronic kidney disease (CKD) have higher prevalence of left ventricular hypertrophy and cardiovascular disease; however, it remains unclear if development of CKD is associated with higher incidence of heart failure, independent from diabetes and hypertension. We analyzed the relations of CKD to incident heart failure and to cardiovascular disease (CVD) death or heart failure (combined end point) in 10 181 Physicians' Health Study male participants (mean age, 67 years).…”
Section: Discussionmentioning
confidence: 99%